1987
DOI: 10.1038/sc.1987.15
|View full text |Cite
|
Sign up to set email alerts
|

Identification of herniated nucleus pulposis in spinal cord injury

Abstract: SummaryFive cases of documented traumatic herniated nucleus pulposis are presented all occurring within the cervical region. The incidence of herniated disc in cervical spinal cord injury is O· 7° o. The incidence of herniated disc in bilateral facet dislo cations is 2·3°0. The common features are radicular pain, incomplete syndrome, and bilateral facet dislocations. A routine myelogram is the most helpful test to establish the diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
4

Year Published

1993
1993
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 15 publications
0
5
0
4
Order By: Relevance
“…Post-traumatic cervical disc herniation into the spinal canal has been reported by different authors [1,2,7]. Eismont et al [4] suggested an algorithm for their treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Post-traumatic cervical disc herniation into the spinal canal has been reported by different authors [1,2,7]. Eismont et al [4] suggested an algorithm for their treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Post-traumatic disc herniation associated with dislocation of the cervical spine is a well-known entity described by several authors [1,2,4,5,7]. Their treatment has become well established to prevent catastrophic iatrogenic complications upon reduction of the fracture-dislocation.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiologie und Ätiologie Die Angaben zur Häufigkeit unfallbedingter Bandscheibenprotrusionen und/oder -prolabierungen differieren z. T. erheblich. Dies ist insbesondere historisch begründet durch die schlechte Sensitivität der vor Jahren herangezogenen Röntgennativdiagnostik und Computertomografie gegenüber der MRT-Bildgebung [1][2][3]. Weiterhin begründen methodische Unterschiede der Studien unterschiedliche Häufigkeitsangaben, die von keinem einheitlichen Unfallbegriff ausgehen und vielfach retrospektive klinische Datenanalysen vorstellen.…”
Section: Gutachtliche Beurteilung Des Traumatischen Bandscheibenvorfaunclassified
“…So variieren für die HWS die Häufigkeiten traumatischer Bandscheibenvorfälle zwischen 0,7 und über 50 % der aufgearbeiteten Fälle. Auf Höhe der LWS zeigten lediglich 0,2 % der operierten Bandscheiben Hinweise auf eine unfallbedingte Genese [1][2][3][4][5]. Publikationen zur Häufigkeit traumatischer Bandscheibenvorfälle unterscheiden sich nach dem zugrunde gelegten Unfallmechanismus (z.…”
Section: Gutachtliche Beurteilung Des Traumatischen Bandscheibenvorfaunclassified
See 1 more Smart Citation